Consumers and palm oil: How much do they know and does it matter how much they know? - Monteiro, Sara Patrícia Pinto (2019)
Corporate social responsibility is a concept present in companies that aim to raise their morals of social progress, respect fundamental rights, protect the environment, and take into consideration the interests of their consumers. The involvement of companies with social responsibility is likely to capture the attention of consumers who are concerned with the aspects mentioned above. The purpose of this research is to evaluate whether corporate social responsibility impacts consumer attitudes and behaviours, regarding the sharing of information by companies about the presence of palm oil in their products and the consequences that that the production of this same oil brings to the environment. For this purpose, a study was developed with the objective of perceiving whether consumers are aware of the environmental consequences of palm oil, seek information about this ingredient and if, when presented with the consequences that palm oil production has on the environment, their attitudes and behaviours in relation to their buying and information seeking habits would change. The results show that the the simple fact of providing information about the negative environmental impact of palm oil's production can affect consumers' purchase intentions. This investigation suggests that companies concerned with social responsibility can have an important role to play by facilitating consumer awareness regarding the negative consequences of the production of palm oil.